Unraveling Hemophilia in the Modern Era: From Pathogenesis to Emerging Therapies - Hridika Jain; Swati Rathore; Nilesh Jain; R.B. Goswami (Current Advances in Medicine, 2026)
Introduction: Hemophilia is a rare X-linked inherited bleeding disorder caused by a deficiency of coagulation factor VIII (hemophilia A) / factor IX (hemophilia B), resulting in impaired clot formation and recurrent bleeding episodes. This review aims to provide a comprehensive overview of the epidemiology, pathophysiology, diagnostic approaches, and evolving therapeutic strategies for hemophilia. It focuses on current treatments, inhibitor complications, and emerging therapies to improve outcomes. Methods: A comprehensive literature review was conducted using established databases, including PubMed, Scopus, Web of Science, and Google Scholar. Particular emphasis was placed on literature covering gene therapy, extended half-life factor concentrates, non-factor therapies, and inhibitor management. Results: The study found that hemophilia primarily affects males and presents with varying degrees of severity. Prophylactic therapy significantly reduces bleeding rates (by ~70-90%) and prevents joint damage. However, inhibitor development (seen in ~20-30% of severe cases) remains a key challenge. Emerging therapies, including non-factor treatments and gene therapy, show substantial improvement in bleeding control and patient quality of life. Discussion: The findings show that effective management of Hemophilia A and B relies on early prophylactic therapy, including extended half-life factor VIII and IX with pharmacokinetic-guided dosing. Inhibitor development remains a major challenge. Emerging therapies, such as Emicizumab, Fitusiran, Concizumab, and gene therapy using AAV vectors and CRISPR approaches, improve outcomes and reduce treatment burden. Conclusion: Hemophilia is a lifelong disorder requiring individualized and evolving treatment strategies. Integration of conventional factor replacement with emerging therapies has significantly improved outcomes and reduced morbidity. This review highlights key challenges, recent advances, and future directions, providing an updated and concise resource for clinical and research applications.